2021
DOI: 10.1097/mpa.0000000000001753
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Medicine in the Management of Pancreatic Cancer

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 92 publications
(337 reference statements)
2
15
0
Order By: Relevance
“…In contrast to Steindorf et al [ 17 ], we can report long-term benefits on physical functioning and health-related QoL even after 6 months follow-up period with prescribed home-based exercises. Our data demonstrate the need for exercise prescriptions to preserve or improve physical functioning during and after pancreatic cancer treatment, and we can show that it’s safe and feasible, given the fact that quite a number of the patients with pancreatic cancer present themselves with frailty or fatigue, sarcopenia and / or weight loss, which generally reduces patients’ QoL and thus having a negative effect on overall survival [ 9 , 40 ]. Furthermore, no negative scores in patients undergoing chemotherapy compared to those without chemotherapy was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Steindorf et al [ 17 ], we can report long-term benefits on physical functioning and health-related QoL even after 6 months follow-up period with prescribed home-based exercises. Our data demonstrate the need for exercise prescriptions to preserve or improve physical functioning during and after pancreatic cancer treatment, and we can show that it’s safe and feasible, given the fact that quite a number of the patients with pancreatic cancer present themselves with frailty or fatigue, sarcopenia and / or weight loss, which generally reduces patients’ QoL and thus having a negative effect on overall survival [ 9 , 40 ]. Furthermore, no negative scores in patients undergoing chemotherapy compared to those without chemotherapy was observed.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are only seven individual published studies focusing exclusively on patients with PanCa. [22][23][24] Of them, only three studies (all without control) have been conducted in patients during NAT (including one single-arm study, 53 one case series 25 and one case report. 26 In addition, among the ongoing exercise trials for patients with PanCa in ClinicalTrial.…”
Section: Discussionmentioning
confidence: 99%
“…57 As a result, a multicomponent programme consisting of clinical-based resistance and aerobic exercises and adapted sport activities will be adopted given the promising results in patients with PanCa undergoing NAT through a combined exercise programme. 24 An exercise intervention of this format has recently been shown to be safe and effective in maintaining…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite promising findings, there is a paucity of clinical data concerning exercise in PanCa. In a recent systematic review by our team (9), we identified only seven separate trials involving only 201 patients with over half being case reports or case series. Although a few trials (10,11) have been reported since our review also favoring exercise in PanCa, there has been no evidence from a setting where broader inclusion criteria and more flexible programs are used as compared with clinical trials under tightly controlled conditions (i.e., explanatory trials).…”
mentioning
confidence: 99%